Politik hukum pendaftaran tanah elektronik pasca undang-undang cipta kerja - Tetama, Androvaga Renandra (Diploma IV Pertanahan Sekolah Tinggi Pertanahan Nasional, 2023)
Implementation of electronic land registration as a form of efficiency, transparency, and accountability in providing public services to the community. So, the purpose of this study is to analyze the legal politics of the electronic land registration system from a regulatory perspective after the publication of the job creation act. The method used is normative legal research with a statutory regulation approach. The results of the study show that after the publication of the job creation act, one of the goals is to reduce overlapping regulations and conflicting norms, which are not achieved, and even become complicated at the implementation level. If there is disharmony between regulations governing electronic land registration, synchronization of regulations is a necessity. Electronic certificates as the final product of land registration as an embodiment of certainty and protection of land have strong, valid, and irrefutable evidence, according to the size of the area and boundaries, and even become valid evidence in court proceedings. The quality of good land data as a measure of the success of electronic land registration has positive sides including efficiency, cheaper land services, accountability, and accessibility. Implementasi pendaftaran tanah elektronik sebagai wujud efisiensi, transparansi dan akuntabilitas dalam melakukan layanan publik kepada masyarakat. Maka tujuan penelitian ini adalah menganalisis politik hukum sistem pendaftaran tanah elektronik dari sisi regulasi setelah terbitnya undang-undang cipta kerja. Metode yang digunakan adalah penelitian hukum normatif dengan pendekatan peraturan perundang-undangan. Hasil penelitian menunjukkan bahwa pasca terbitnya undang-undang cipta kerja salah satunya tujuannya adalah mengurangi tumpang tindih regulasi dan konflik norma tidak tercapai, bahkan menjadi keruwetan sendiri dalam tataran pelaksanaannya. adanya disharmoni di antara regulasi yang mengatur pendaftaran tanah elektronik, maka sinkronisasi regulasi merupakan sebuah keniscayaan. Sertifikat elektronik sebagai produk akhir pendaftaran tanah sebagai mewujudkan kepastian dan perlindungan atas tanah memiliki bukti yang kuat, valid dan tidak terbantahkan, sesuai ukuran luas dan batas-batasnya, bahkan menjadi alat bukti yang sah dalam proses peradilan. Kualitas data pertanahan yang baik sebagai tolak ukur keberhasilan pendaftaran tanah elektronik yang memiliki sisi positif diantarnya efisiensi, layanan pertanahan lebih murah, akuntabilitas dan aksesibilitas.